(untitled) (REMUNOM, 2025)
This study analyzes how sexual education, when treated seriously in schools, can be an important ally in preventing and protecting against child sexual abuse, especially within the family environment. The choice of this topic is justified by the high number of cases recorded in the domestic context, generally committed by people close to the victims. Given this worrying reality, it is essential to discuss the role of educational actions in strengthening the knowledge, awareness and empowerment of children and adolescents. The research was based on theoretical studies, official data and Brazilian legislation that deals with the topic, which made it possible to carry out an analysis of the main factors involved, such as the profile of victims and aggressors, and the transformative potential of knowledge as a form of protection. It is observed that, although the National Common Curricular Base (BNCC) does not treat sexual education as an isolated subject, the topic can be addressed through the so-called integrative themes. The results of the study indicate that, by addressing sexuality in a transversal manner in the school curriculum, it is possible to reduce the vulnerability of young people and strengthen support and protection networks inside and outside the school.